Edukasi Hipertensi terhadap Pengetahuan, Kepatuhan Minum Obat, dan Tekanan Darah pada Pasien Hipertensi - Gusti Ayu Made Sulassri; M.Dinah Charlota Lerik; Noorce Ch Berek; Luh Putu Ruliati; Christina R. Nayoan (Institut Penelitian Matematika, Komputer, Keperawatan, Pendidikan dan Ekonomi (IPM2KPE), 2023)
This study aims to analyze the effectiveness of hypertension education on the level of knowledge, adherence to medication, and blood pressure in hypertensive patients. This research method is Quasi-Experimental, with the design being One-group pre-test and post-test. The results showed that the level of knowledge, adherence to taking medication, and blood pressure were p=0.000 (p<0.05). In conclusion, hypertension education effectively increases knowledge, medication adherence, and blood pressure in hypertensive patients. Keywords: Education, Hypertension, Medication Compliance, Knowledge, Blood pressure.